Thermal, Structural, and Physical Properties of Freeze Dried Tropical Fruit Powder. (22nd December 2014) - Athmaselvi, K. A.; Kumar, C.; Balasubramanian, M.; Roy, Ishita
Abstract : This study evaluates the physical properties of freeze dried tropical (guava, sapota, and papaya) fruit powders. Thermal stability and weight loss were evaluated using TGA-DSC and IR, which showed pectin as the main solid constituent. LCR meter measured electrical conductivity, dielectric constant, and dielectric loss factor. Functional groups assessed by FTIR showed presence of chlorides, and O–H and N–H bonds in guava, chloride and C–H bond in papaya, and chlorides, and C=O and C–H bonds in sapota. Particle size and type of starch were evaluated by X-ray diffraction and microstructure through scanning electronic microscopy. A semicrystalline profile and average particle size of the fruit powders were evidenced by X-ray diffraction and lamellar/spherical morphologies by SEM. Presence of A-type starch was observed in all three fruits. Dependence of electric and dielectric properties on frequency and temperature was observed.